Lithium ion battery and energy storage device

By introducing active substances with specific spatial distribution coefficients into the positive electrode sheet and the negative electrode sheet of the lithium-ion battery, the dynamic performance matching between the positive electrode and the negative electrode is solved, which is difficult to determine the cycle stability of the lithium-ion battery in the prior art. The problem is to achieve efficient and simple cycle stability evaluation and excellent battery performance.

CN119230726AActive Publication Date: 2024-12-31XIAMEN HITHIUM ENERGY STORAGE TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411375376.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-31
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently and easily determine the cycle stability of lithium-ion batteries, and it usually requires charging and discharging tests to confirm it after assembly into a battery.

Method used

By introducing active substances with specific spatial distribution coefficients into the positive electrode sheet and the negative electrode sheet, the dynamic performance matching between the positive electrode and the negative electrode is ensured, and specifically, by controlling the number, particle size distribution and pore distribution of the active substance, the positive and negative electrodes are defined. The ratio of the spatial distribution coefficient is within the range of 1.5 to 3.3.

Benefits of technology

The excellent cycle stability of lithium-ion batteries is achieved, so that the transmission rate of lithium ions between the positive electrode plate and the negative electrode plate is matched, and the interfacial lithium-ion separation and side reactions can be avoided, so that it can be easily determined efficiently after making the positive and negative electrode plate. Cycling stability performance avoids the problem of dynamic mismatch after improvement of single pole sheet.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230726A_ABST
    Figure CN119230726A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a lithium ion battery and an energy storage device. The lithium ion battery comprises a pole piece with an active substance, the active substance has a spatial distribution coefficient eta in the pole piece, and eta = a * gamma / zeta; a is equal to 100, gamma is equal to Dn50 / (Dn100-Dn00), Dn00, Dn50 and Dn100 are the sizes of the active substances when the active substances account for 0%, 50% and 100%, and the unit is mu m; zeta = 1-Dtap / Dtrue, Dtap and Dtrue are tap density and true density of the active substance, and the unit is g / cm < 3 >; the pole piece comprises a positive pole piece containing a positive active material and a negative pole piece containing a negative active material, the positive active material is lithium iron phosphate, the positive active material has a first spatial distribution coefficient eta positive on the positive pole piece, the negative active material has a second spatial distribution coefficient eta negative on the negative pole piece, and 1.5 < = eta positive / eta negative < = 3.3.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a lithium-ion battery and an energy storage device. Background Art

[0002] In the research of lithium-ion batteries, the cycle stability of lithium-ion batteries is a key performance indicator, which is directly related to the service life and reliability of lithium-ion batteries. At present, most of the improvements are only made to the positive electrode or only to the negative electrode, in an attempt to affect the overall performance of lithium-ion batteries through the performance improvement of a single electrode. However, the impact of the performance improvement of a single electrode on the cycle stability of the entire battery needs to be confirmed by charging and discharging tests after assembling into a lithium-ion battery. It can be seen from this that it is difficult to efficiently and easily determine whether a lithium-ion battery has excellent cycle stability with current technology. Summary of the invention

[0003] In order to solve the above technical problems, the embodiments of the present application provide a lithium-ion battery and an energy storage device. By providing a lithium-ion battery with a positive electrode plate and a negative electrode plate having matching kinetic properties, a lithium-ion battery with excellent cycle stability can be obtained more efficiently and simply.

[0004] In a first aspect, an embodiment of the present application provides a lithium-ion battery, the lithium-ion battery comprising a pole piece having an active material, the active material having a spatial distribution coefficient η in the pole piece, η=a*γ / ζ;

[0005] Wherein, a=100;

[0006] Wherein, γ=Dn50 / (Dn100-Dn00), Dn00 is the size of the active substance corresponding to when the amount of the active substance accounts for 0%, in μm, Dn100 is the size of the active substance corresponding to when the amount of the active substance accounts for 100%, in μm, and Dn50 is the size of the active substance corresponding to when the amount of the active substance accounts for 50%, in μm;

[0007] ζ = 1-D tap / D true , the D tap is the tap density of the active substance, in g / cm 3 , the D true is the true density of the active substance in g / cm 3 ;

[0008] The electrode sheet comprises a positive electrode sheet having a positive electrode active material and a negative electrode sheet having a negative electrode active material, wherein the positive electrode active material is lithium iron phosphate, and the positive electrode active material has a first spatial distribution coefficient η in the positive electrode sheet. 正 The negative electrode active material has a second spatial distribution coefficient η in the negative electrode sheet 负 , 1.5≤η 正 / η 负 ≤3.3.

[0009] Furthermore, 1.5≤η 正 / η 负 ≤2.8.

[0010] Furthermore, for the negative electrode active material, 0.7 μm≤Dn00≤1.2 μm, 1.5 μm≤Dn50≤2.5 μm, and 20 μm≤Dn100≤50 μm.

[0011] Furthermore, the tap density of the negative electrode active material satisfies 1.0 g / cm 3 ≤D tap ≤1.3g / cm 3 .

[0012] Furthermore, the true density of the negative electrode active material satisfies 2.0 g / cm 3 ≤D true ≤2.3g / cm 3 .

[0013] Furthermore, for the positive electrode active material, 0.10 μm≤Dn00≤0.30 μm, 0.70 μm≤Dn50≤1.0 μm, and 3.4 μm≤Dn100≤5.0 μm.

[0014] Furthermore, the tap density of the positive electrode active material satisfies 0.8 g / cm 3 ≤D tap ≤1.4g / cm 3 .

[0015] Furthermore, the true density of the positive electrode active material satisfies 3 g / cm 3 ≤Dtrue≤3.8g / cm 3 .

[0016] Further, the negative electrode active material includes one or more of graphite, hard carbon, silicon carbon, silicon negative electrode, and carbon microspheres; and / or,

[0017] The positive electrode active material is prepared by a ferric phosphate solid phase method, an iron red process solid phase method, a ferrous oxalate process method or a liquid phase method; and / or,

[0018] The negative electrode active material is graphite, which is obtained by grinding, screening, shaping, granulating and graphitizing carbon-based raw materials. The graphite is primary particles and / or secondary particles.

[0019] In a third aspect, the present application provides an energy storage device, which includes the battery isolation membrane as described in the first aspect, or the energy storage device includes a battery isolation membrane prepared by the preparation method of the battery isolation membrane as described in the second aspect.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention aims at two parameters of active materials that have an important influence on the contact area of ​​electrolyte, namely, the number particle size distribution and the pore distribution, and constructs a spatial distribution coefficient η=a*γ / ζ of the active materials, and limits the ratio of the spatial distribution coefficients of the positive and negative electrodes to satisfy: 1.5≤η 正 / η 负 ≤3.3, which has the following advantages: First, it makes the transfer rate of lithium ions between the positive electrode and the negative electrode have a high matching, so that the lithium-ion battery can obtain excellent cycle stability; second, because the above-mentioned spatial distribution coefficient can be determined by the number particle size distribution and pore distribution of the active substance, the stability of the cycle performance of the lithium-ion battery can be determined more efficiently and simply, and there is no need to assemble the electrodes into a battery and then test it to determine the cycle stability; third, because the kinetic performance matching between the positive and negative electrodes is fully considered, the situation that the kinetics is greatly improved after the improvement of a single electrode, but the other electrode is not improved, but the kinetics are not matched, and the cycle stability cannot be effectively improved will not occur. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0023] Figure 1 is a structural schematic diagram of a household energy storage system according to an embodiment of the present application;

[0024] Figure 2 It is a structural schematic diagram of an energy storage system according to an embodiment of the present application.

[0025] Figure numerals: 100, energy storage system; 10, energy storage device; 20, electric energy conversion device; 30, first user load; 40, second user load; 50, high-voltage cable; 60, first electric energy conversion device; 70, second electric energy conversion device. DETAILED DESCRIPTION

[0026] In the present invention, the directions or positional relationships indicated by the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inner", "outer", "middle", "vertical", "horizontal", "lateral", "longitudinal" and the like are based on the directions or positional relationships shown in the drawings. These terms are mainly used to better describe the present invention and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific direction, or to be constructed and operated in a specific direction.

[0027] In addition, some of the above terms may be used to express other meanings in addition to indicating orientation or positional relationship. For example, the term "on" may also be used to express a certain dependency or connection relationship in some cases. For those skilled in the art, the specific meanings of these terms in the present invention can be understood according to specific circumstances.

[0028] In addition, the terms "installed", "set", "provided with", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral structure; it can be a mechanical connection, or an electrical connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be an internal connection between two devices, elements, or components. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0029] In addition, the terms "first", "second", etc. are mainly used to distinguish different devices, elements or components (the specific types and structures may be the same or different), and are not used to indicate or imply the relative importance and quantity of the indicated devices, elements or components. Unless otherwise specified, "plurality" means two or more.

[0030] The technical solution of the present invention will be further described below in conjunction with embodiments.

[0031] As the core components of lithium-ion batteries, the material properties of positive and negative electrodes have a decisive influence on the cycle stability of lithium-ion batteries. Related technologies often only focus on the performance improvement of a single electrode, but lithium-ion batteries have two types of electrodes, positive and negative electrodes, which affect each other during the charging and discharging process. Therefore, the performance improvement of a single electrode affects the performance of the entire battery. It is necessary to assemble the lithium-ion battery and conduct charge and discharge tests to confirm the cycle stability of the battery. This also reflects that it is difficult to efficiently and easily determine whether a lithium-ion battery has excellent cycle stability based on the structural characteristics of a single electrode and its active material.

[0032] Based on an in-depth analysis of the problems existing in the prior art, the present application provides a lithium-ion battery and an energy storage device, which can efficiently and simply enable lithium ions to obtain excellent cycle stability by exploring the kinetic performance matching between the positive electrode active material and the negative electrode active material.

[0033] In a first aspect, an embodiment of the present application provides a lithium-ion battery, comprising a pole piece having an active material, wherein the active material has a spatial distribution coefficient η in the pole piece, η=a*γ / ζ;

[0034] Where, a=100;

[0035] Wherein, γ=Dn50 / (Dn100-Dn00), Dn00 is the size of the active material corresponding to the amount of the active material accounting for 0%, in μm, Dn100 is the size of the active material corresponding to the amount of the active material accounting for 100%, in μm, and Dn50 is the size of the active material corresponding to the amount of the active material accounting for 50%, in μm;

[0036] ζ=1-D tap / D true , D tap is the tap density of the active substance, in g / cm 3 , D true is the true density of the active substance in g / cm 3 ;

[0037] The electrode sheet includes a positive electrode sheet having a positive electrode active material and a negative electrode sheet having a negative electrode active material, and the positive electrode active material has a first spatial distribution coefficient η in the positive electrode sheet. 正 The negative electrode active material has a second spatial distribution coefficient η in the negative electrode sheet. 负 , 1.5≤η 正 / η 负 ≤3.3.

[0038] Among them, 1.5≤η 正 / η 负 ≤3.3 includes any point value within the above ratio range, for example, ≤η 正 / η 负 is 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3 or 3.3.

[0039] The lithium-ion battery of the embodiment of the present application controls the first spatial distribution coefficient η of the positive electrode active material. 正 The second spatial distribution coefficient η of the negative electrode active material 负The ratio between them is in the range of 1.5 to 3.3, which can well match the kinetic performance of the positive electrode and the negative electrode, making the transmission of lithium ions between the positive and negative electrodes more balanced. This can avoid the problem of lithium precipitation and serious side reactions at the interface of the negative electrode caused by the mismatch of lithium ion transmission rate, and achieve precise control of the diffusion capacity of lithium ions between the positive electrode and the negative electrode, thereby improving the cycle stability of lithium-ion batteries.

[0040] Among them, the spatial distribution coefficient η of the active material in the electrode can reflect the lithium ion diffusion capacity of the positive electrode and the negative electrode, which determines the transmission rate of lithium ions between the electrodes. The stronger the lithium ion diffusion capacity, the faster the transmission rate. 正 / η 负 When controlled within the range of 1.5 to 3.3 in the embodiment of the present application, the lithium ion diffusion capacity on one side of the positive electrode sheet and the one side of the negative electrode sheet has good matching, so that the lithium ions transmitted from the positive electrode sheet to the negative electrode sheet can be more appropriately embedded in the negative electrode sheet, and there will not be too many lithium ions precipitated at the interface of the negative electrode sheet, nor will it cause too many side reactions at the negative electrode sheet. It can be seen that by accurately controlling the diffusion capacity of lithium ions in the positive electrode sheet and the negative electrode sheet, a lithium ion battery with good cycle stability can be obtained.

[0041] When η 正 / η 负 When η is less than 1.5, it indicates that the lithium ion transfer rate on the positive electrode side is higher than that on the negative electrode side. This makes it easy for the number of lithium ions transferred from the positive electrode to the negative electrode to exceed the capacity of the negative electrode to receive and store lithium ions, which leads to excess lithium ions on the negative electrode side, making it very easy for interfacial lithium precipitation to occur, and ultimately causing cycle performance degradation. 正 / η 负 When it is greater than 3.3, it indicates that the lithium ion transfer rate on the positive electrode side is lower than that on the negative electrode side, which makes the amount of lithium ions transferred from the positive electrode to the negative electrode insufficient to fully utilize the lithium ion storage capacity of the negative electrode. At this time, the negative electrode has higher kinetics, resulting in a more serious side reaction between the material on the negative electrode and the electrolyte, which in turn leads to serious and irreversible lithium loss, and ultimately leads to the deterioration of the battery cycle performance.

[0042] In addition, in the embodiment of the present application, the spatial distribution coefficient η=a*γ / ζ, where a is a constant, γ=Dn50 / (Dn100-Dn00), ζ=1-D tap / D true. It can be seen that the spatial distribution coefficient of the embodiment of the present application can be jointly defined by the two structural characteristics of the number particle size distribution and pore distribution of the active material, thereby more efficiently, simply and intuitively reflecting the diffusion ability of lithium ions inside the active material. Among them, γ = Dn50 / (Dn100-Dn00) is the number distribution coefficient of the active material, and ζ is the maximum pore ratio formed when the active material is most densely packed. The above two parameters mainly affect the contact area between the positive and negative active materials and the electrolyte, and then affect the diffusion ability of lithium ions in the positive and negative electrodes. It can be understood that since the spatial distribution coefficient η of the present application includes the first spatial distribution coefficient η of the positive electrode active material in the positive electrode sheet 正 , and the second spatial distribution coefficient η of the negative electrode active material in the negative electrode sheet 负 , so η 正 and η 负 All satisfy a*γ / ζ. The first spatial distribution coefficient is determined by the number particle size distribution and the void distribution of the positive electrode active material, and the second spatial distribution coefficient is determined by the number particle size distribution and the void distribution of the negative electrode active material.

[0043] In summary, the present invention aims at two parameters that have an important influence on the contact area of ​​the electrolyte by the active material, namely, the number particle size distribution and the pore distribution, and constructs a spatial distribution coefficient η = a*γ / ζ of the active material, and limits the ratio of the spatial distribution coefficients of the positive and negative electrodes to satisfy: 1.5≤η 正 / η 负 ≤3.3. First, the transfer rate of lithium ions between the positive electrode and the negative electrode has a high matching, so that the lithium-ion battery can obtain excellent cycle stability. Second, since the above-mentioned spatial distribution coefficient can be determined by the number particle size distribution and pore distribution of the active material, there is no need to assemble the electrodes into a battery for testing to determine the cycle stability. Third, since the kinetic performance matching between the positive and negative electrodes is fully considered, the situation that the kinetics of a single electrode is greatly improved after improvement, but the other electrode is not improved, but the kinetics are not matched, and the cycle stability cannot be effectively improved will not occur.

[0044] Therefore, the embodiment of the present application can screen and determine the degree of matching of the kinetic performance of the positive and negative electrodes after the production, which helps to efficiently and easily determine the cycle stability performance of the lithium-ion battery, and further facilitates the rapid screening and optimization of the adaptation degree of the positive and negative electrodes used, and obtains a lithium-ion battery with excellent cycle stability.

[0045] Furthermore, 1.5≤η 正 / η 负 ≤2.8.

[0046] Since the spatial distribution coefficient η of the active material is closely related to the diffusion capacity of lithium ions, it can intuitively reflect the influence of the positive and negative electrode active materials on the balance and diffusion efficiency of lithium ion diffusion. Therefore, the embodiment of the present application further optimizes η. 正 / η 负 The ratio range is 1.5 to 2.8, which can achieve better cycle stability.

[0047] Further, for the negative electrode active material, 0.7 μm ≤ Dn00 ≤ 1.2 μm, 1.5 μm ≤ Dn50 ≤ 2.5 μm, and 20 μm ≤ Dn100 ≤ 50 μm. Exemplarily, for the negative electrode active material, Dn00 is 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, or 1.2 μm, Dn50 is 1.5 μm, 1.6 μm, 1.8 μm, 2.0 μm, 2.2 μm, or 2.5 μm, and Dn100 is 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, or 50 μm.

[0048] Further, for the positive electrode active material, 0.10 μm ≤ Dn00 ≤ 0.30 μm, 0.70 μm ≤ Dn50 ≤ 1.0 μm, and 3.4 μm ≤ Dn100 ≤ 5.0 μm. Exemplarily, for the positive electrode active material, Dn00 is 0.10 μm, 0.12 μm, 0.15 μm, 0.20 μm, 0.25 μm, or 0.30 μm, Dn50 is 0.70 μm, 0.75 μm, 0.80 μm, 0.85 μm, 0.90 μm, 0.95 μm, or 1.0 μm, and Dn100 is 3.4 μm, 3.8 μm, 4.0 μm, 4.2 μm, 4.5 μm, 4.8 μm, or 5.0 μm.

[0049] When the particle size distribution of the number of negative electrode active materials and positive electrode active materials is within the above range, it is more conducive to controlling the particle size distribution of the number of active materials in the appropriate γ range, thereby obtaining a lithium-ion battery with excellent cycle stability. Among them, the wider the γ range, the more large and small particles of active materials will be. The increase in the number of small particle active materials will aggravate the degree of side reactions. The narrower the γ range, the fewer large and small particles of active materials are. Although this is conducive to further improving the cycle stability of lithium-ion batteries, it will reduce the yield of active materials, increase the production cost of lithium-ion batteries, and is not conducive to actual production.

[0050] It should be noted that in the embodiments of the present application, by controlling the above-mentioned number particle size distribution range of the positive electrode active material and the negative electrode active material, the overall uniformity of the active material can be better reflected, and the uniform particle size can be used to assist in maintaining the stability of the pole piece structure, which is also conducive to improving the cycle stability of the lithium-ion battery. As for the actual space occupied by the active material particles in the pole piece, the embodiments of the present application are controlled by the parameter ζ of the maximum pore volume formed when the active material is accumulated, thereby limiting the coordination of the number particle size distribution and the pore distribution to more intuitively and simply predict the balanced matching of the positive and negative pole pieces to the lithium ion transmission rate. In addition, compared with the volume particle size distribution, the embodiments of the present application use the number particle size distribution to regulate the dynamic performance of the positive and negative pole pieces because the number particle size distribution better reflects the role of small particle active materials, so the coordination of the number particle size distribution and the pore distribution is conducive to more accurately regulating the lithium ion transmission efficiency.

[0051] Furthermore, the tap density of the negative electrode active material satisfies 1.0 g / cm 3 ≤D tap ≤1.3g / cm 3 For example, the tap density D of the negative electrode active material is tap 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 or 1.3 g / cm 3 .

[0052] Furthermore, the true density of the negative electrode active material satisfies 2.0 g / cm 3 ≤D true ≤2.3g / cm 3 For example, the true density D of the negative electrode active material is true 2.0g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 or 2.3g / cm 3 .

[0053] Furthermore, the tap density of the positive electrode active material satisfies 0.8 g / cm 3 ≤D tap ≤1.4g / cm 3 For example, the tap density D of the positive electrode active material is tap 0.8g / cm 3 , 1.0g / cm 3 , 1.2g / cm 3 or 1.4 g / cm 3 .

[0054] Furthermore, the true density of the positive electrode active material satisfies 3 g / cm 3 ≤D true ≤3.8g / cm 3 For example, the true density D of the positive electrode active material is true 3g / cm 3 、3.2g / cm 3 , 3.5g / cm 3 、3.6g / cm 3 or 3.8g / cm 3 .

[0055] By controlling the tap density and true density of the positive and negative active materials within the above range, it is beneficial to better control the pore distribution range of the active materials with a suitable ζ range under the densest packing condition, avoiding the difficulty of electrolyte infiltration due to too small pores, or the difficulty of increasing the compaction density of the electrode due to too large pores, thereby affecting the capacity level and energy density and other performance of the lithium-ion battery.

[0056] Optionally, the positive electrode active material includes one or more of lithium iron phosphate, lithium iron manganese phosphate, and lithium-rich manganese-based. Preferably, the positive electrode active material is lithium iron phosphate. Lithium iron phosphate is prepared by an iron phosphate solid phase method, an iron red process solid phase method, a ferrous oxalate process method, or a liquid phase method.

[0057] For example, in an optional embodiment, when the positive electrode active material is lithium iron phosphate, the preparation method of lithium iron phosphate includes the following steps:

[0058] The solid phase process is adopted to grind and mix the precursor iron source, lithium source and carbon source in proportion, and then prepare the finished lithium iron phosphate product after spray granulation, sintering and crushing. In the above process, the particle size of the precursor can be adjusted by adjusting the grinding time of the raw materials, and the primary particle size of the final product can be controlled according to the sintering temperature and time. Finally, the sintered material is crushed into a finished powder with a certain particle size distribution through the crushing process. The particle size distribution of the powder is mainly controlled by the sintering temperature and time. Crushing is to open the agglomerated secondary particles to form dispersed primary particles; the tap density and true density are determined by the primary particle size of the powder. Smaller primary particle size tends to reduce the tap density and true density of the powder material.

[0059] Optionally, the negative electrode active material includes one or more of graphite, hard carbon, silicon carbon, silicon negative electrode, and carbon microspheres. Preferably, the negative electrode active material is graphite. Graphite is obtained by grinding, screening, shaping, granulating, and graphitizing carbon-based raw materials, and the graphite is primary particles and / or secondary particles.

[0060] For example, in an optional embodiment, when the negative electrode active material is graphite, the method for preparing the graphite includes the following steps:

[0061] The required graphite is obtained by grinding, screening, shaping, granulating and graphitizing the raw material low-sulfur coke or medium-sulfur coke. The particle size distribution during grinding, screening, shaping and granulating of the raw material is the main factor affecting the particle size distribution and tap density of graphite. In addition, the tap density is also affected by the degree of graphitization. The true density of graphite is related to the type of raw material and the graphitization process. Usually, there is no significant difference in the true density of graphite after the same type of raw materials are completely graphitized.

[0062] It should be noted that the active material of the embodiments of the present application can also be prepared by other conventional methods in the art, and the present application does not limit the preparation method of the positive electrode active material (such as lithium iron phosphate) and the negative electrode active material (such as graphite).

[0063] Related technologies often focus on structural modification of active materials in the electrode, such as functional coating design of core-shell structure of positive electrode active materials, to improve the performance of positive electrode. However, such modified materials often require complex synthesis processes, and there are risks of poor structural stability such as cracking or film peeling during use, and they are often not compatible with existing lithium-ion battery manufacturing processes and equipment, making it difficult to directly apply such solutions in actual production.

[0064] The present application uses the above-mentioned positive electrode active material and negative electrode active material, especially the preferred lithium iron phosphate and graphite, which can be selected from the positive electrode active material and negative electrode active material commonly used in the field, without further structural modification of the material. In this way, the embodiment of the present application does not need to design a complex structure for the active material, and only needs to make the number particle size distribution and pore distribution of the conventional active material meet the spatial distribution coefficient η = a*γ / ζ of the present application, and ensure η 正 / η 负 When the ratio is within the range of 1.5 to 3.3, the lithium-ion battery can have excellent cycle stability. This material selection feature makes the lithium-ion battery of the embodiment of the present application more suitable for practical industrial applications.

[0065] In a second aspect, an embodiment of the present application further provides an energy storage device 10, which includes the battery isolation membrane described in the first aspect or the second aspect.

[0066] Taking electrochemical energy storage as an example, an embodiment of the present application provides an energy storage device 10, which has a group of chemical batteries in it. The chemical elements in the batteries are mainly used as energy storage media. The charging and discharging process is accompanied by chemical reactions or changes in the energy storage media. In simple terms, the electricity generated by wind and solar energy is stored in chemical batteries. When the use of external electricity reaches a peak, the stored electricity is released for use, or transferred to places where electricity is scarce for use.

[0067] The current energy storage (i.e., energy storage) application scenarios are relatively wide, including energy storage on the power generation side, energy storage on the grid side, and energy storage on the power consumption side. The corresponding types of energy storage devices 10 include:

[0068] (1) Large-scale energy storage power stations applied to wind power and photovoltaic power stations can help renewable energy generation meet grid connection requirements and improve the utilization rate of renewable energy. As a high-quality active / reactive regulating power source on the power supply side, energy storage power stations can achieve load matching of electric energy in time and space, enhance the ability to absorb renewable energy, reduce instantaneous power changes, reduce the impact on the power grid, improve the absorption of new energy generation, and are of great significance in power grid system backup, relieving peak load power supply pressure, and peak and frequency regulation.

[0069] (2) Energy storage containers used on the grid side mainly perform peak load regulation, frequency regulation, and grid congestion relief. They can achieve peak load shaving and valley filling of power loads, that is, charging the energy storage batteries when the power load is low and releasing the stored power during the peak load period, thereby achieving a balance between power production and consumption;

[0070] (3) Small energy storage cabinets used on the power consumption side, the main functions are self-generation and self-use of electricity, peak-valley price difference arbitrage, capacity cost management and improving power supply reliability. According to different application scenarios, energy storage on the power consumption side can be divided into industrial and commercial energy storage cabinets, household energy storage devices 10, energy storage charging piles, etc., which are generally used in conjunction with distributed photovoltaics. Industrial and commercial users can use energy storage for valley-peak price difference arbitrage and capacity cost management. In the power market that implements peak-valley electricity prices, by charging the energy storage system 100 when the electricity price is low and discharging the energy storage system 100 when the electricity price is high, peak-valley electricity price difference arbitrage is achieved to reduce electricity costs. In addition, industrial enterprises that are subject to two-part electricity prices can use the energy storage system 100 to store energy during low electricity consumption and discharge it during peak load, thereby reducing peak power and the maximum demand reported, and achieving the purpose of reducing capacity electricity charges. Household photovoltaic storage can improve the level of self-generation and self-use of electricity. Due to high electricity prices and poor power supply stability, the demand for household photovoltaic installations is driven. Considering that photovoltaic power is generated during the day, and users generally have higher loads at night, energy storage can be configured to better utilize photovoltaic power, improve the level of self-generation and self-use, and reduce electricity costs. In addition, communication base stations, data centers and other fields need to configure energy storage for backup power.

[0071] See also Figure 1 , Figure 1This is a structural diagram of a household energy storage system 100 of an embodiment of the present application. The present application provides a household energy storage system 100, which includes an electric energy conversion device 20 (photovoltaic panel), a first user load 30 (street lamp), a second user load 40 (such as air conditioners and other household appliances), and an energy storage device 10. The energy storage device 10 is a small energy storage box that can be mounted on an outdoor wall by wall hanging. Specifically, the photovoltaic panel can convert solar energy into electric energy during the period of low electricity prices. The energy storage device 10 is used to store the electric energy and supply it to street lamps and household appliances for use during peak electricity prices, or to supply power when the power grid is off / power outage.

[0072] See also Figure 2 , Figure 2 is a schematic diagram of the structure of an energy storage system 100 according to an embodiment of the present application, and the present application Figure 2 The embodiment is described by taking the shared energy storage scenario on the power generation / distribution side as an example, and the energy storage device 10 of the present application is not limited to the energy storage scenario on the power generation / distribution side.

[0073] The present application provides an energy storage system 100, which includes: a high-voltage cable 50, a first electric energy conversion device 60, a second electric energy conversion device 70 and an energy storage device 10 provided by the present application. In the case of power generation, the first electric energy conversion device 60 and the second electric energy conversion device 70 are used to convert other forms of energy into electric energy, connect with the high-voltage cable and supply it to the power distribution network for use. When the power load is low and the first electric energy conversion device 60 and the second electric energy conversion device 70 generate excess power, the excess power is stored in the energy storage device 10, reducing the wind and light abandonment rates and improving the problem of new energy power generation and consumption; when the power load is high, the power grid issues an instruction to use the power stored in the energy storage device 10 in conjunction with the high-voltage cable 50 to transmit the power to the power consumption side in a grid-connected mode, providing peak load regulation, frequency regulation, standby and other services for the operation of the power grid, giving full play to the peak load regulation of the power grid, promoting the peak load reduction and valley filling of the power grid, and alleviating the power supply pressure of the power grid.

[0074] Optionally, the first electric energy conversion device 60 and the second electric energy conversion device 70 can convert at least one of solar energy, light energy, wind energy, thermal energy, tidal energy, biomass energy and mechanical energy into electric energy.

[0075] The number of energy storage devices 10 can be multiple, and multiple energy storage devices 10 are connected in series or in parallel. Multiple energy storage devices 10 are supported and electrically connected by isolation plates (not shown). In this embodiment, "multiple" refers to two or more. An energy storage box can also be provided outside the energy storage device 10 to accommodate the energy storage device 10.

[0076] Optionally, the energy storage device 10 may include but is not limited to a battery module, a battery pack, a battery system, etc. The actual application form of the energy storage device 10 provided in the embodiment of the present application may be but is not limited to the listed products, and may also be other application forms. The embodiment of the present application does not strictly limit the application form of the energy storage device 10. The embodiment of the present application only takes the energy storage device 10 as a multi-core battery as an example for explanation. When the energy storage device 10 is a single battery, the energy storage device 10 may be at least one of a cylindrical battery, a square battery, etc.

[0077] The solution of the present application will be further introduced below in conjunction with specific embodiments and experimental data.

[0078] Example 1

[0079] This embodiment provides a lithium ion battery, which is obtained by the following method.

[0080] Preparation of positive electrode sheet: lithium iron phosphate, conductive carbon black, and polyvinylidene fluoride are dispersed in N-methylpyrrolidone at a mass ratio of 95:3:2 and mixed evenly to obtain positive electrode slurry, and the positive electrode slurry is evenly coated on the positive electrode collector; after drying, cold pressing, slitting, cutting and other processes, the positive electrode sheet is obtained. The structural parameters of the positive electrode active material lithium iron phosphate are shown in Table 1.

[0081] Preparation of negative electrode sheet: Graphite, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber are dispersed in a solvent at a mass ratio of 96:1.5:1.5:1 and mixed evenly to obtain negative electrode slurry, and the negative electrode slurry is applied to the negative electrode current collector; after drying, cold pressing, slitting and cutting, the negative electrode sheet is obtained. The structural parameters of the negative electrode active material graphite are shown in Table 1.

[0082] Preparation of electrolyte: In an argon atmosphere glove box with a moisture content of ≤1ppm, ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) are mixed in a volume ratio of 1:1:1 to obtain a mixed solvent, and then dry lithium salt LiPF6 is added thereto to prepare an electrolyte with a concentration of 1 mol / L.

[0083] Diaphragm: 16μm polyethylene diaphragm is used.

[0084] Assembly of lithium-ion batteries: stack the above-mentioned positive electrode sheets, separators, and negative electrode sheets in order so that the battery separator is in the middle of the positive electrode and the negative electrode to separate the positive electrode sheets and the negative electrode sheets. After winding, a bare battery cell is obtained. After connecting the electrode ears, the battery cell is assembled into an outer package. After injecting the above-mentioned electrolyte, the battery cell is packaged, allowed to stand, formed, shaped, and capacity tested, etc., to finally prepare a lithium-ion battery.

[0085] Embodiment 2 to Embodiment 6

[0086] Compared with Example 1, the difference between Examples 2 to 6 is that the structural parameters of the positive electrode active material and the negative electrode active material are different, as shown in Table 1. In Example 6, the total mass of the negative electrode active material is the same, and the mass of hard carbon accounts for 2%.

[0087] Comparative Example 1 to Comparative Example 2

[0088] Compared with Example 1, the difference between Comparative Examples 1 and 2 is that the structural parameters of the positive electrode active material and the negative electrode active material are different, see Table 1 for details.

[0089] <Performance Test>

[0090] (1) Particle size distribution test of active material: The positive electrode active material and the negative electrode active material of Examples 1 to 6 and Comparative Examples 1 to 2 were measured using a laser particle size analyzer (model: Malvern Mastersizer 3000) according to the particle size distribution laser diffraction method (GB / T19077-2016) to obtain Dn00, Dn50, and Dn100.

[0091] (2) Tap density test of active substances

[0092] The prepared sample is placed in a graduated cylinder and the graduated cylinder is fixed on a mechanical vibration device (instrument model Dandong Better BT-313). The vibration motor drives the mechanical vibration device to vibrate vertically up and down. The graduated cylinder containing the sample vibrates rhythmically with the mechanical vibration device. When the number of vibrations reaches the set number, the mechanical vibration device stops vibrating and the volume of the graduated cylinder is read. According to the definition of density: mass divided by volume, the tap density of the positive electrode active material / negative electrode active material after tapping is calculated.

[0093] (3) True density test of active substances

[0094] When measuring the sample, the instrument (instrument model BEST 3H-2000TD) automatically collects and records the pressure P1 and volume V1 of the reference chamber; puts a sample of a certain unknown volume V into the sample test chamber with a known volume V2, injects a certain amount of gas into the reference chamber and records the pressure P2 after stabilization; connects the sample test chamber with the reference chamber and records the pressure P3 after stabilization, and calculates the volume Vsample of the sample to be measured based on the pressure value after equilibrium stabilization and the related known volumes V1 and V2. According to the definition of density: mass divided by volume, the true density of the positive electrode active material / negative electrode active material can be calculated.

[0095] (4) Battery cycle stability test: The lithium ion batteries of Examples 1 to 6 and Comparative Examples 1 and 2 were subjected to a charge and discharge cycle test on a charge and discharge instrument.

[0096] In an environment of 25°C, constant power charging is performed at a charging power of 1P until the upper limit voltage reaches 3.65V, then constant voltage charging is performed, and then constant power discharge is performed at a discharge power of 1P until the final voltage is 2.5V, and the first cycle discharge capacity of the battery is recorded; then 500 charge and discharge cycles are performed, and the discharge capacity of the 500th cycle is recorded. The calculation formula for the capacity retention rate is: capacity retention rate after the 500th cycle = (discharge capacity after the 500th cycle / first cycle discharge capacity) × 100%.

[0097] Table 1 Structural parameters and test results of Examples 1 to 6 and Comparative Examples 1 to 2

[0098]

[0099]

[0100] According to the above test results, η 正 / η 负 When the η is controlled within the range of 1.5 to 3.3, the capacity retention rate is high, reaching more than 95.12%. In particular, when it is controlled within the range of 1.5 to 2.8, the capacity retention rate can be further increased to more than 96.46%, indicating that the transfer rate of lithium ions between the positive electrode and the negative electrode is highly matched, so that the lithium-ion battery has a high level of cycle stability. 正 / η 负 The ratio is too small, and η in Comparative Example 2 正 / η 负 The larger ratio reflects that the transmission rate of lithium ions between the positive electrode and the negative electrode is not matched, which may cause problems such as lithium deposition on the interface and serious side reactions, leading to a decrease in cycle performance.

[0101] The technical solutions disclosed in the embodiments of the present invention are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the technical solutions and core ideas of the present invention. At the same time, for those skilled in the art, according to the ideas of the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A lithium ion battery, characterized in that: The lithium-ion battery comprises a pole piece having an active material, wherein the active material has a spatial distribution coefficient η in the pole piece, η=a*γ / ζ; Wherein, a=100; Wherein, γ=Dn50 / (Dn100-Dn00), Dn00 is the size of the active substance corresponding to when the amount of the active substance accounts for 0%, in μm, Dn100 is the size of the active substance corresponding to when the amount of the active substance accounts for 100%, in μm, and Dn50 is the size of the active substance corresponding to when the amount of the active substance accounts for 50%, in μm; ζ = 1-D tap / D true , the D tap is the tap density of the active substance, in g / cm 3 , the D true is the true density of the active substance in g / cm 3 ; The electrode sheet comprises a positive electrode sheet having a positive electrode active material and a negative electrode sheet having a negative electrode active material, wherein the positive electrode active material is lithium iron phosphate, and the positive electrode active material has a first spatial distribution coefficient η in the positive electrode sheet. 正 The negative electrode active material has a second spatial distribution coefficient η in the negative electrode sheet 负 , 1.5≤η 正 / η 负 ≤3.

3.

2. The lithium-ion battery according to claim 1, characterized in that 1.5≤η 正 / or 负 ≤2.8。 3. The lithium-ion battery according to claim 1, characterized in that For the negative electrode active material, 0.7 μm≤Dn00≤1.2 μm, 1.5 μm≤Dn50≤2.5 μm, and 20 μm≤Dn100≤50 μm.

4. The lithium-ion battery according to claim 1, characterized in that: The tap density of the negative electrode active material satisfies 1.0 g / cm 3 ≤D tap ≤1.3g / cm 3 .

5. The lithium-ion battery according to claim 1, characterized in that: The true density of the negative electrode active material satisfies 2.0 g / cm 3 ≤D true ≤2.3g / cm 3 .

6. The lithium-ion battery according to claim 1, characterized in that For the positive electrode active material, 0.10 μm≤Dn00≤0.30 μm, 0.70 μm≤Dn50≤1.0 μm, and 3.4 μm≤Dn100≤5.0 μm.

7. The lithium-ion battery according to claim 1, characterized in that: The tap density of the positive electrode active material satisfies 0.8 g / cm 3 ≤D tap ≤1.4g / cm 3 .

8. The lithium-ion battery according to claim 1, characterized in that The true density of the positive electrode active material satisfies 3 g / cm 3 ≤D true ≤3.8g / cm 3 .

9. The lithium-ion battery according to claim 1, characterized in that: The negative electrode active material includes one or more of graphite, hard carbon, silicon carbon, silicon negative electrode, and carbon microspheres; and / or, The positive electrode active material is prepared by a ferric phosphate solid phase method, an iron red process solid phase method, a ferrous oxalate process method or a liquid phase method; and / or, The negative electrode active material is graphite, which is obtained by grinding, screening, shaping, granulating and graphitizing carbon-based raw materials. The graphite is primary particles and / or secondary particles.

10. An energy storage device, characterized in that: The energy storage device comprises a lithium-ion battery as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Secondary battery and electric device

    CN115395081A

  • Secondary battery and electric equipment

    CN116314601A

  • Secondary battery and electric equipment

    CN116365013A

  • Solvent-free process for preparing lithium-ion batteries

    WO2024196971A1

Cited By

  • Lithium-ion battery and energy storage apparatus

    WO2026066443A1